The Frequency and Causes of Visual Impairment and Blindness among Middle and Older Population - Mazhar-ul-Hassan, Farnaz Siddiqui, Saba Alkhairy (Pakistan Journal of Ophthalmology, 2017)
Purpose: To estimate the frequency and causes of visual impairment and blindness in middle and older age groups. Study Design: Retrospective study (hospital based data). Place and Duration of Study: Eye department of Dow university hospital (Ojha campus), Dow international medical college, Dow university of health sciences, Karachi, Pakistan Purpose: To estimate the frequency and causes of visual impairment and blindness in middle and older age groups. Study Design: Retrospective study (hospital based data). Place and Duration of Study: Eye department of Dow university hospital (Ojha campus), Dow international medical college, Dow university of health sciences, Karachi, Pakistan